A Trama Verde e Azul: transitando entre a abstração e a experiência urbana - Ana Mourão Olveira (2019)
This thesis was motivated by the desire to make a critical analysis of the planning of urban green areas which, as of the 1990's, conformed a tendency of approaching two epistemological fields until then considered in opposition: urban and environmental studies. Because they are based on principles of landscape ecology, widely used in planning of protected areas, most of the proposals are not able to deal with the challenges of the social and political dimensions of the urban issue, which lends them a scientificist and fragmented character, disconnected from the urban complexity. In spite of an important literature dedicated to criticizing urban planning and preservationist policies, critics of the proposals in this urban-environmental boundary are scarce. In order to contribute to this reflection, this thesis was dedicated to the study of the Green and Blue Network proposed in the scope of the Belo Horizonte Metropolitan Region planning and three correlated initiatives: one at the Nord-Pas-de-Calais Mining Basin region and one in the Lille Metropolitan Area, both in France; and another one in the city of Vitoria-Gasteiz, in Spain. The critical analysis was constructed through the transit between the abstract dimension — of the thought, the imagination, the plan — and the urban experience — of the lived, the action, the event. As a result, a detailed study of the proposals and their historical, political and ideological contexts was made, taking as reference Henri Lefebvre's theory of the social production of space and some other authors from the critical urban planning field. Some social practices were also identified that align with the utopian projections of the Green and Blue Network, related to the overcoming of the city-nature dichotomy and the collective appropriation of urban spaces.